2018
DOI: 10.1007/s00455-018-9894-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nasogastric Tube on Aspiration Risk: Results from 147 Patients with Dysphagia and Literature Review

Abstract: Nasogastric tube (NGT) is a common feeding strategy for patients at risk of endotracheal aspiration with an oral diet. With NGT feeding, however, swallowing of small amounts saliva cannot be avoided. We investigated whether the aspiration rate when swallowing 1 mL of fluid increased in patients using an NGT in different dysphagia severities. One hundred forty-seven patients who had been receiving NGT feeding underwent a videofluoroscopic swallowing study (VFSS). During VFSS, subjects were offered 1 mL of fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
0
19
0
3
Order By: Relevance
“…The number of comorbidities was significantly associated with aspiration in this study. A randomized controlled trial concluded that stroke, traumatic brain injury, Parkinson disease and dementia may cause aspiration in patients receiving nasogastric feeding (Kim et al, 2018). This study showed that although the same factors were reserved in both models, indwelling days and food type were reserved in the CART model and the use of sedative-hypnotics was reserved in the nomogram model.…”
Section: Ta B L Ementioning
confidence: 85%
See 3 more Smart Citations
“…The number of comorbidities was significantly associated with aspiration in this study. A randomized controlled trial concluded that stroke, traumatic brain injury, Parkinson disease and dementia may cause aspiration in patients receiving nasogastric feeding (Kim et al, 2018). This study showed that although the same factors were reserved in both models, indwelling days and food type were reserved in the CART model and the use of sedative-hypnotics was reserved in the nomogram model.…”
Section: Ta B L Ementioning
confidence: 85%
“…The difficulties in medical treatment and nursing caused by aspiration pose challenges to the quality management provided by the medical system. Some studies have revealed that the swallowing of saliva and regurgitated gastric contents that occurs during nasogastric feeding may result in aspiration (Kim et al, 2018;Torsy et al, 2018…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9). Eine eventuell liegende nasogastrale Sonde muss für die Untersuchung nicht entfernt werden [15,16] (▶ Video 2).…”
Section: Schritt 6 Konsistenzprüfungunclassified